Interpretasi Konstitusi Dalam Pengujian Konstitusionalitas Untuk Mewujudkan The Living Constitution - Hapsoro, Fakhris Lutfianto; Ismail, Ismail (UI Scholars Hub, 2020)
The constitutional authority granted to the Constitutional Court by Article 24C paragraph (1) in the third amendment to the 1945 Constitution in the test of constitutional law against the constitution provides automatically over authority in giving the interpretation of the 1945 Constitution to the Constitutional Court. Associated with the interpretation of the constitution, then a constitution is not only considered to be a documented constitution but can be transformed into the living constitution. In practice in Indonesia, it can be found the decisions of the Constitutional Court who use constitutional interpretation to assess the constitutionality of a norm as in Decision No. 005 / PUU-IV / 2006, Decision No. 14 / PUU-XI-2013, and Decision No. 138 / PUU-VII / 2009. Based on this, then in this paper will outline the extent to which the efforts of judges in realizing the living constitution through the interpretation of the judge in the constitutionality of which can be analyzed through the decisions of the Constitutional Court.